Spectrophotometric evaluation of three-layered acrylic teeth discoloration caused by selected food dyes – in vitro study - Barzyk, Magdalena; Grychowska, Natalia; Więckiewicz, Włodzimierz (Journal of Stomatology, 2017)
Introduction. The overall aesthetic result in the use of removable prostheses is correlated with a type of artificial teeth and their ability to maintain aesthetics and colour stability. The issue of the influence of food on acrylic teeth structure and degree of its discoloration over time is an interesting research problem. Aim of the study. To evaluate the formation and intensity of discoloration of three-layered acrylic teeth caused by food dyes from tested solutions. Methods. The study material consisted of a group of 90 three-layered acrylic teeth. Samples were immersed in black tea and dry red wine for six months. The control group was immersed in distilled water and consisted of 30 samples of three-layered acrylic teeth. The teeth were subjected to spectrophotometric examination at baseline, after 24 hours, 7 days, 14 days, 1 month, 4 months and 6 months. Results. Three-layered acrylic teeth changed the shade following immersion in black tea for six months. Changes in the brightness of teeth samples submerged in red wine appeared on the second spectrophotometric examination and continued in subsequent assessments. In the control group, over time there was systematic shift of the shades to group D. There were also individual brightness shifts towards brighter shades but there were slightly larger shifts towards darker ones. Conclusion. Three-layered acrylic teeth are subject to discoloration. Both black tea and red wine induce colour changes, more intense for the latter substance.